Fine-scale spatial and temporal variations in insecticide resistance in Culex pipiens complex mosquitoes in rural south-eastern Tanzania - Nancy S. Matowo; Said Abbasi; Givemore Munhenga; Marcel Tanner; Salum A. Mapua; David Oullo; Lizette L. Koekemoer; Emanuel Kaindoa; Halfan S. Ngowo; Maureen Coetzee; Jürg Utzinger; Fredros O. Okumu (Parasites & Vectors, 2019)
Abstract Background Culex mosquitoes cause considerable biting nuisance and sporadic transmission of arboviral and filarial diseases. Methods Using standard World Health Organization procedures, insecticide resistance profiles and underlying mechanisms were investigated during dry and wet seasons of 2015 and 2016 in Culex pipiens complex from three neighbouring administrative wards in Ulanga District, Tanzania. Synergist tests with piperonyl butoxide, diethyl maleate, and triphenyl phosphate, were employed to investigate mechanisms of the observed resistance phenotypes. Proportional biting densities of Culex species, relative to other taxa, were determined from indoor surveillance data collected in 2012, 2013, and 2015. Results Insecticide resistance varied significantly between wards and seasons. For example, female mosquitoes in one ward were susceptible to bendiocarb and fenitrothion in the wet season, but resistant during the dry season, while in neighbouring ward, the mosquitoes were fully susceptible to these pesticides in both seasons. Similar variations occurred against bendiocarb, DDT, deltamethrin, and lambda-cyhalothrin. Surprisingly, with the exception of one ward in the wet season, the Culex populations were susceptible to permethrin, commonly used on bednets in the area. No insecticide resistance was observed against the organophosphates, pirimiphos-methyl and malathion, except for one incident of reduced susceptibility in the dry season. Synergist assays revealed possible involvement of monooxygenases, esterases, and glutathione S-transferase in pyrethroid and DDT resistance. Morphology-based identification and molecular assays of adult Culex revealed that 94% were Cx. pipiens complex, of which 81% were Cx. quinquefasciatus, 2% Cx. pipiens, and 3% hybrids. About 14% of the specimens were non-amplified during molecular identifications. Female adults collected indoors were 100% Cx. pipiens complex, and constituted 79% of the overall biting risk. Conclusions The Cx. pipiens complex constituted the greatest biting nuisance inside people’s houses, and showed resistance to most public health insecticides possible. Resistance varied at a fine geographical scale, between adjacent wards, and seasons, which warrants some modifications to current insecticide resistance monitoring strategies. Resistance phenotypes are partly mediated by metabolic mechanisms, but require further evaluation through biochemical and molecular techniques. The high densities and resistance in Culex could negatively influence the acceptability of other interventions such as those used against malaria mosquitoes.